The teaching of ethics and core values in chemistry education - Apotheker Jan (Chemistry Teacher International)
This special issue is deciated to the teaching of ethics in chemistry education. In this editorial the articles in this special issue are introduced. A short explanation how they fit into this specific special issue is given.